Autobiographical Memories as Islands of Certainty in an Ocean of Complexity: A Cooperative Enquiry on the Effects of the COVID-19 Emergency on Some Disability Services in Northern Italy - Cuppari, Antonella (INSTED: Interdisciplinary Studies in Education & Society, 2021)
In a historical moment characterised by uncertainty and concern about the future, autobiographical memories can be a source of inspiration for orientation and learning to change. In social work, this possibility becomes a necessity that cannot be postponed, especially where the usual patterns of action prove inadequate to deal with the problems generated by the crisis. Within the framework of a systemic epistemology and complexity, this contribution describes a cooperative inquiry involving some coordinators of disability services in Lombardy, Northern Italy. The re-enactment of autobiographical memories was used as a basis to explore themes related to the professional practices of these coordinators. The memories, recalled and re-signified within the training device, facilitated the opening to a complex thought, in which certainty and uncertainty and different ways of knowledge are connected.